CHALLENGES IN TUBERCULOSIS COINFECTION TREATMENT IN PEOPLE WITH HIV/AIDS IN ANGOLA - Cameia,Silvano da Silva (2020)
ABSTRACT Objective: to know the challenges faced during tuberculosis coinfection treatment in people with HIV/AIDS (HIV/TB) in Huambo, Angola. Method: this is a qualitative convergent-care investigation carried out in the antituberculosis dispensary of the sanatorium hospital of Huambo, Angola. It included 18 people co-infected with HIV/TB and 11 health professionals. Data were collected from January to July 2016 through conversation interviews, participatory observation and a convergence group. In data analysis, conventional content analysis of Hsieh and Shannon was used. Results: the data originated two categories: challenges of HIV/TB coinfected people when facing the diseases and treatment adherence, and challenges due to intervening factors upon HIV/TB treatment adherence. Conclusions: people’s conception about living with HIV/TB, associated with the intervening factors upon HIV/TB treatment adherence, results in late search for health services, non-adherence to treatment and worsening of diseases, thus posing as challenges to be overcome for better control of this double epidemic.